INBREEDING ESTIMATION AT DIFFERENT STAGES OF RAISING UKRAINIAN RED DAIRY BREED OF CATTLE - Pidpala, T. V.; Shevchuk, N. P. (Scientific Progress & Innovations, 2019)
Investigating the effectiveness of using inbreeding is important at different stages of raising the Ukrainian Red dairy breed of cattle. Generally accepted zoo-technical methods (individual milk production recording), laboratory (determining milk quality composition), retrospective analysis (indices for the entire period of animal using), variation-statistical method (determining sign parameters) were used during the research. As a result of studying related breeding, milk productivity of inbred cows was analyzed at different levels and outbred cows during three stages of raising the Ukrainian Red dairy breed. It was found that related breeding was used most intensively during the first two stages: the proportion of inbred cows was 21.4 % and 40.4 %. It is explained by the purpose of breeding, i.e. the creation of a stable heredity in animals concerning butterfat content owing to the use of the Angler’s breed gene pool. The primary influence on the level of milk productivity in cows of close and distant inbreeding degrees during the first and second lactations was determined. The consolidating effect of related selection is manifested by the signs of fat content in milk. Its high value (3.89– 4.10 %) is observed in cows during the first two stages of breeding. Some decrease of butterfat content in animals during the third stage is explained by the involvement of the Holstein breed gene pool in the breeding process. As to the manifestation of milk productivity, inbred cows are not inferior to outbred ones, and even sometimes dominate them, indicating the absence of inbred depression. Theoretical and practical statements on the effectiveness of using inbreeding of various levels during the creation and consolidation of the Ukrainian Red dairy breed of cattle were further developed. The obtained results should be taken into account while selecting the Ukrainian Red dairy breed at the stage of its consolidation and improvement.